(untitled) (Research, Society and Development, 2020)
Introduction: Considering the increase in cesarean section in Brazil is not only linked to false medical indications, but is also related to a decision by the pregnant woman herself, this article has an objective to comprehend the aspects that interfere in the woman’s preference for cesarean section. Methodology: This is a descriptive study, with a qualitative approach, which is linked to a matrix research project entitled “Experience of preparing for childbirth and its repercussions on the co-construction of women’s autonomy”. The research was carried out in a Family Health Unit (USF) in the city of Cuiabá, capital of Mato Grosso, where eight pregnant women participated in the study. The data were by semi-structured interviews with open and closed questions about the subject, analyzing the thematic type content. Results: By analyzing the data, two categories were emerged: a) the decision by cesarean section and b): agents that influence the woman’s information process. Final Considerations: The decision process for the type of delivery is surrounded by doubts, desires, beliefs and expectations. The educative role of the health professional in prenatal care allows women the opportunity to develop a critical, conscious and autonomous sense allowing them to decide on the various possibilities of experiencing the parturition process based on relevant information and with strong scientific evidence.